Temperature, placental abruption and stillbirth. (October 2019) - Rammah, Amal; Whitworth, Kristina W.; Han, Inkyu; Chan, Wenyaw; Hess, Judy Wendt; Symanski, Elaine
Abstract: Background: Pregnant women may be vulnerable to changes in ambient temperature and warming climates. Recent evidence suggests that temperature increases are associated with placental abruption, a risk factor for stillbirth. Objectives: We investigated the effect of acute exposures to apparent temperature on stillbirths in Harris County, Texas, 2008–2013. Methods: We conducted a case-crossover study to investigate the association between temperature and stillbirth among 708 women. We used data from the National Climatic Data Center to estimate maternal exposure to daily average apparent temperature over the days (lag days 1 through 6) preceding the stillbirth event. We employed symmetric bidirectional sampling to select six control periods one to three weeks before and after each event and applied conditional logistic regression to examine associations between increases of apparent temperature and stillbirths during the warm season (May–September). We adjusted for fine particulate matter (PM2.5 ), nitrogen dioxide (NO2 ) and ozone (O3 ) and used stratified analysis to examine differences in risk by maternal race/ethnicity. We also examined the association among stillbirths with and without placental abruptions. Results: Independent of air pollutant exposures, a 10 °F increase in apparent temperature in the week preceding delivery (lag days 1 to 6) was positively associated with a 45% (adjusted OR = 1.45, 95% confidence interval (CI): 1.18, 1.77) increase in risk for stillbirth. Risks were elevated for stillbirths occurring in June through August, for Hispanic and non-Hispanic Black women, but not for non-Hispanic Whites. We also observed elevated risks associated with temperature increases in the few days preceding delivery among stillbirths caused by placental abruption, with the risk being highest on lag day 1 (OR = 1.93, 95% CI: 1.15, 3.23). Conclusions: Independent of maternal ambient air pollutant exposure, we found evidence of an association between apparent temperature increases in the week preceding an event and risk of stillbirth. Risks for stillbirth varied by race/ethnicity. Further, in the first study to evaluate the impact of temperature on a specific complication during pregnancy, the risks were higher among mothers with placental abruption. Highlights: Increased temperature in the week preceding delivery was associated with stillbirth risk. Stillbirth risk varied by maternal race/ethnicity. Increased temperature was associated with risk of stillbirths by placental abruption.